2012
DOI: 10.3747/co.19.851
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Cohort Study to Determine Perceived Patient Benefit in Providing Custom Breast Prostheses

Abstract: ConclusionsThe qualitative data provide a strong case in support of the new device. Patient demand, perceived benefit, and experience wearing the prosthesis were documented. Suggestions for improvements in the device and in the program operations were gathered and will influence future development of this service. KEY WORDSMastectomy, custom breast prosthesis, mixed methodology, cancer rehabilitation, quality of life

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…Our study can be corroborated by Kubon et al (2012) which found similar data, not presenting any changes in sexual activity nor in the relationship with partners. Study realized with aim to compare hysterectomy and mastectomy patients in terms of depression, body image, sexual problems and spouse relations, showed that women with mastecotomy was associated with more depression and not present sexual problems (Keskin and Gumus, 2011).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our study can be corroborated by Kubon et al (2012) which found similar data, not presenting any changes in sexual activity nor in the relationship with partners. Study realized with aim to compare hysterectomy and mastectomy patients in terms of depression, body image, sexual problems and spouse relations, showed that women with mastecotomy was associated with more depression and not present sexual problems (Keskin and Gumus, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Kubon et al (2012), in a research with 19 patients who used external prosthesis, concluded that the most common differences in the group referred to the disease (cancer), the treatment, the feeling of being feminine and attractive, and to sexual activity. Although these differences are visible, there was no statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At our cancer centre, a new type of external custom-designed breast prosthesis was developed (Kubon, McClennen, Fitch, McAndrew, & Anderson, 2011). The evaluation of this new product provided an opportunity to explore women's perspectives about external breast prostheses.…”
Section: Purposementioning
confidence: 99%
“…Unfortunately, losing part of or the entire breast through surgery (for both breast conserving surgery and mastectomy) often leads to further problems during the recovery period, including psychosocial morbidity (anxiety, depression, body image/self-image, distress, anxiety, sexuality, and self-esteem) [47][48][49]. In addition, breast cancer patients often choose to avoid reconstructive surgery because of finances, physical conditions, or the recovery time [50]. For these women, external breast prosthesis (EBP) has been shown to be an effective solution [51] and is used by up to 90% of women after surgery in western countries [50].…”
Section: Practical Example: External Breast Prosthesismentioning
confidence: 99%